The Implementation of National Convention Event of PR Indonesia 2018 in Facing the Challenge of PR 4.0 - Novi Erlita (IJRDO - Journal of Social Science and Humanities Research, 2019)
Referring to the global predictions of consultants in the next 12 years, Indonesia will become one of the 5 countries in the world with the largest economy. All indicators and research suggest Indonesia is heading towards that. All economists forecast that Indonesia in the near future will be in line with developed countries such as Japan, China, India, Australia and South Korea. Public Relations (PR) practitioners can become Public Relations 4.0 and build the Indonesia Brand. How Public Relations 4.0 Communication-PR Indonesia is currently able to align Indonesian names synonymously with Global Brand and the strength of Global Economy. The Implementation National Convention Events of Public Relations Indonesia 2018 in the Challenge PR 4.0. In the Information Center show at the evens, for the needs of the factual and actual as well as give you an idea related to what kind of an overview of the range of its continuous efforts to build trust are keywords and strategic step in the world of PR. Warren Buffet statement about the importance of maintaining the reputation was also based on efforts to cultivate trust. In this paper using a type of qualitative research with the analysis of descriptive data in the first phase of this study, the writer obtained data as well as the facts of the events or activities that have been carried out in the form of units of the analysis in-depth interviews are not just limited to a list of questions but also for research into resource/ key informants in directly.